Maximum Scope for Mini Paper and Strawboard Mills in Madhya Pradesh - Seth, V. K. (Indian Forester, 1975)
Due to an escalation in prices of paper and paper boards, there is a scramble for the establishment of mini paper and strawboard units in the country. Madhya Pradesh, by virtue of its central geographical situation, happy power position, plentiful availability of water and substantial incentives and concessions offered, could well be the first choice for investment decisions. In this article a case has been made out for the establishment, during the next five years, of 10 mini paper units of 10 tonnes per day capacity and the same number of mini strawboard units in Madhya Pradesh, indicating their locations and pointing out their contribution to the country in general and the State in particular.